Intestinal inflammation markers in inflammatory bowel disease - Alomair, Abdullatif; Alswayeh, Ayman; Alhazmi, Abrar; Alshammari, Abdullah; Alsaffar, Salma; Falamarzi, Abrar; Alothman, Moath; Rayes, Lujain; Alkhathami, Mohammed; Alhamidah, Ali (International Journal Of Community Medicine And Public Health, 2018)
During the past few decades, extensive researches were conducted to identify serological markers in patients with inflammatory bowel disease (IBD) that can reliably diagnose and monitor disease activity and help in predicting relapses. To date, several serological markers have been identified. This review will address the different serological markers and their clinical significance and applicability in medical practice. Serological markers include antibodies against microbial antigens, peptide antigens, autoantibodies, and basic inflammatory markers. Some serological markers such as anti-Saccharomyces cerevisiae antibodies (ASCA) and antibodies against exocrine pancreas (PAB) help the confirmation of the diagnosis of IBD to differentiate it from other non-IBD. Perinuclear anti-neutrophil cytoplasmic antibodies (pANCA) and ASCA can distinguish Chron’s disease and ulcerative colitis. Certain markers can aid stratification of Chron’s disease including antibodies to Pseudomonas fluorescens associated sequence I2 (Anti-I2), antibodies to bacterial flagellin (Anti-CBir1), ASCA, and antibodies to outer membrane porin C (Anti-OmpC). ASCA and pANCA can predict disease response to therapeutic agents (e.g. Infliximab). ASCA can also unaffected family members at risk of developing Chron’s disease.